Ofendículos e suas implicações no direito penal brasileiro - Silva, Gracieli Firmino da (2006)
Defending juridical goods has always been one of the human major priorities, so that both private and public prosecution must be performed respectively by the individual or by the State to strengthen democracy or to legitimate justice. The major interest of preserving them is due to the individual while the State acts in a secondary way, helping him and providing him conditions to act, to execute when he provokes the jus puniendi, or his due right for punishment. Thus, the proprietor of the juridical goods uses pre-established defense mechanisms so-called brianbackers, or "offendicula", by doctrine. It is concerning an area which is still in need of research. The right of private prosecution is inherent to the individual as his defense and it is guaranteed by the Federal Constitution. The moderate use of brianbackers characterizes a justifiable cause which will exclude the antijuridicity of a fortuitous legal fact considered as typical which can happen. However, if there is an excess in its usage, the proprietor can probably be considered criminally responsible for acting with guilty intent, recklessness, or with strict liability, except if the error is generated in an excusable way. The results provided by the data make us conclude that brianbackers represent a pre-established self-defense which authorizes the defendant to make use of them always in moderation